Violence Against Women in Tribal and Marginalized Communities - Dr. Rachna Shrivastava,; Dr. Vinita Singh, (International Journal of Scientific Research in Science and Technology, 2026)
Violence against women in tribal and marginalized communities represents one of the most neglected dimensions of gender-based violence. Women belonging to Scheduled Tribes, Scheduled Castes, nomadic groups, migrant populations, and other marginalized communities face layered vulnerabilities arising from gender inequality, social exclusion, poverty, illiteracy, and weak institutional access. Their experiences of violence often remain invisible due to geographical isolation, cultural silence, lack of awareness, and limited engagement with formal legal systems. This research paper examines the nature, causes, and changing perceptions of violence against women in tribal and marginalized communities within a sociological framework. The study is based on primary data collected from a sample of 300 respondents using a structured questionnaire, supplemented by secondary sources such as books, academic journals, government reports, and international agency publications. Five research objectives guide the study, focusing on awareness levels, forms of violence, reporting behaviour, institutional response, and perceptions of gender justice. Data analysis is presented through five tables aligned with each objective. The theoretical framework draws upon Patriarchy Theory, Intersectionality Theory, Feminist Theory, Social Exclusion Theory, and Cultural Relativism to understand the structural and cultural dimensions of violence. A review of eight significant studies highlights the persistence of violence and the limitations of policy interventions in marginalized contexts. The findings reveal that violence against women in tribal and marginalized communities is shaped by intersecting factors of gender, caste, ethnicity, poverty, and isolation. While awareness is gradually increasing, traditional norms, fear of authority, and institutional neglect continue to restrict reporting and justice. The paper concludes with policy-oriented recommendations emphasizing culturally sensitive interventions, legal outreach, education, and community participation to address violence against women in marginalized settings.
Keywords: Violence Against Women; Tribal Communities; Marginalized Groups; Intersectionality; Gender Inequality; Sociological Study